Janssen effect in dynamic particulate systems - Windows-Yule, C. R. K.; Mühlbauer, Sebastian; Torres Cisneros, Luis Armando; Nair, Prapanch; Marzulli, Valentina; Pöschel, Thorsten (Physical Review E, 2019)
The Janssen model of stress redistribution within laterally bounded particulate assemblies is a longstanding and valuable theoretical framework, widely used in the design of industrial systems. However, the model relies on the assumption of a static packing of particles and has never been tested in a truly dynamic regime nor for a constraining system whose geometry is dynamically altered. In this paper, we explore the pressure distributions of granular beds housed within a container possessing a laterally mobile sidewall, allowing the depth, height, and cross-sectional areas of the systems studied to be dynamically altered, thus, inducing particle rearrangements and flow in the particulate system constrained thereby. We demonstrate that the systems studied can be successfully described by the Janssen model across a wide range of system expansion rates, including those for which liquidlike flow is clearly observed and propose an extension to the model allowing for an improved characterization of constrained dynamic systems.
CRIS-Team WoS Importer:2019-09-06